2008
DOI: 10.1007/s10409-007-0122-1
|View full text |Cite
|
Sign up to set email alerts
|

A note on the numerical simulations of flow past a wavy square-section cylinder

Abstract: The flow past a square-section cylinder with a geometric disturbance is investigated by numerical simulations. The extra terms, due to the introduction of mapping transformation simulating the effect of disturbance into the transformed Navier-Stokes equations, are correctly derived, and the incorrect ones in the previous literature are pointed out and analyzed. Furthermore, the relationship between the vorticity, especially on the cylinder surface, and the disturbance is derived and explained theoretically. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…It may cause the flow to be unsteady irregular vortex flow with some turbulent behavior or suppress the Kármán vortex shedding, making wake flow steady state. Similar behavior and results can be found in the experiments of cylinder wake transition by Williamson 1 and DNS results on wake vortex dynamics behind a wavy square-section cylinder by Darekar and Sherwin, 8 and Ling and Lin, 24 respectively. ͑6͒ There are many close similarities and common features in the mechanism responsible for the generation of vortex dislocation and related flow phenomena between the present wake-type flow evolution and the cylinder wake transition given by previous studies.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It may cause the flow to be unsteady irregular vortex flow with some turbulent behavior or suppress the Kármán vortex shedding, making wake flow steady state. Similar behavior and results can be found in the experiments of cylinder wake transition by Williamson 1 and DNS results on wake vortex dynamics behind a wavy square-section cylinder by Darekar and Sherwin, 8 and Ling and Lin, 24 respectively. ͑6͒ There are many close similarities and common features in the mechanism responsible for the generation of vortex dislocation and related flow phenomena between the present wake-type flow evolution and the cylinder wake transition given by previous studies.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
“…Fluids 21, 073604 ͑2009͒ mechanism for suppression of the Kármán vortex shedding between the present results and those DNS results of flow around a wavy square cylinder given by Darekar and Sherwin, 8 Ling and Lin, 24 and Lin. 25 Those recent studies of square cylinder wake have demonstrated that once the spanwise wavy disturbance is imposed on the geometry of a straight cylinder, both vertical and streamwise vortices are generated on the cylinder surface.…”
Section: -11supporting
confidence: 70%
See 1 more Smart Citation
“…Based on experimental tests, Bearman & Owen (1998) at a Reynolds number Re = 4 × 10 4 found that the front-face-wavy square cylinder with a wavelength λ / D m = 5.6 and a waviness a / D m = 0.25 can completely suppress vortex shedding and substantially reduce time-mean drag force by up to 30 %. For the front- and rear-face-wavy square cylinder ( λ / D m = 1–10, a / D m ≤ 0.75), Darekar & Sherwin (2001 a , b ) and Ling & Lin (2008) in numerical simulations ( Re = 10–180) observed pairs of opposite-sign streamwise vortices along the spanwise direction, associated with wide and narrow wakes at the saddle and node planes, respectively. It was further found that the wavy cylinder with λ / D m = 5.6 can attain a time-mean drag reduction of up to 16 % at a / D m = 0.129–0.168 ( Re = 100), 21.6 % at a / D m = 0.167 ( Re = 100) and 25.7 % at a / D m = 0.167 ( Re = 180).…”
Section: Introductionmentioning
confidence: 99%
“…Flow around the wavy cylinder with a square cross-section has been studied experimentally and numerically in the literature. The wavy surface was implemented on the front face (Bearman & Owen 1998), on both front and rear faces (Darekar & Sherwin 2001 a , b ; Ling & Lin 2008; Lin, Bai & Alam 2015) or on both lateral side faces (Lam et al. 2012; Lin et al.…”
Section: Introductionmentioning
confidence: 99%